Effect of Polyalcohol on the Gelation Time and Gel Structure of Silk Fibrion (Journal of Fiber Bioengineering and Informatics, 2018)
The Bombyx mori silk fibroin gels were prepared by adding various types of polyalcohol (Ethylene glycol, Polyethylene glycol 600) into the regenerated silk fibroin aqueous solution. The gelation time was recorded respectively. Gel structure was analyzed by X-ray diffraction, Fourier transform infrared spectroscopy, laser Raman spectroscopy and scanning electron microscopy. It was found that adding polyalcohol into the regenerated silk fibroin aqueous solution can accelerate the gelation process, with increase in the percentage of the polyalcohol except at 100%. Silk fibroin gels with Ethylene glycol mainly consist of silk II crystal structure. Ethylene glycol almost has no effect on the molecular conformation or crystal structure of silk fibroin gels. However, adding PEG600 to the solution can promote the silk fibroin molecules to form clusters rapidly, while it can also obstruct the structural transformation of silk fibroin molecules from random coil or α-helix to β-sheet. The crystallinity of silk gels was found to decline with an increase in the adding percentage of PEG600. While adding 100% polyalcohol of the mass of silk fibroin into the solution, whether it was Ethylene glycol or PEG600, the silk fibroin gels have more uniform morphology and pores distribution.
Keywords: Silk fibroin; gel; gelation time; ethylene glycol; PEG 600; polyalcohol; structure